Input-output model-based water footprint indicators to support IWRM in the irrigated drylands of Uzbekistan, Central Asia - Bekchanov, Maksud; Lamers, John P.A.; Bhaduri, Anik; Lenzen, M.; Tischbein, B. (2016)
Water scarcity due to increasing water demand triggered by population growth and irrigation expansion versus a limited and increasingly variable water supply as a consequence of climate change is presently one of the global challenges. This is exemplified in Uzbekistan, Central Asia, where irrigated agriculture is the primary source of the livelihoods of the rural population that makes more than 60 % of all inhabitants. Yet, socio-economic and ecological challenges keep growing, also due to the inefficient management of water resources. Therefore, options to increase water use efficiency were analyzed while considering the entire supply chain of products including the production, processing, consumption and trade stages and processes. These options were analyzed through an elaborated environmentally extended input-output model. The options examined throughout the entire supply chain included: (i) implementing advanced field-level water saving technologies, (ii) increasing crop diversity through expanding fruits and vegetables production and reducing the area of current dominant crops (cotton and paddy rice in downstream), (iii) fostering the further development of less-water demanding agricultural processing industries, (iv) upgrading production value chains by expanding the production of the commodities with higher values added, (v) reducing production and consumption losses, and (vi) diversifying exports by replacing the current cotton fiber exports with cotton commodities of higher values added. The findings may spur decision-makers to formulating strategic priorities at national level and coordinating water uses considering comprehensively technical, economic and ecological aspects along the entire supply chain, which is a key element of IWRM concepts. However, it is argued that increasing water use efficiency through technological and economic transformation reforms necessitates the empowerment of water users, raising their awareness for, and providing the institutional and market infrastructure, which is in-line with IWRM principles as well.